Rebus Sic Stantibus and the Treaty of Waitangi? - Bennett, Mark; Roughan, Nicole (Victoria University of Wellington Law Review, 2006)
The question of the continuing significance of the Treaty of Waitangi is one to which neither legal practice nor scholarship has offered a definitive answer. The question is often regarded as less legal than political; a question of intercultural justice to be contested in the political realm. From within the law, however, the suggestion that the Treaty ought to be reassessed in light of modern circumstances was revived in 2005 when Jeremy Waldron, then University Professor at Columbia University, offered the international law doctrine of rebus sic stantibus as a possible tool for analysis. This article responds to Professor Waldron’s suggestion that the Treaty might be considered overridden by a fundamental change in political circumstances. It first argues that the structuring logic which Professor Waldron advocates is a misreading of the "signpost" which international law offers towards the role of treaties in problems of intercultural justice. The article then presents a comparative assessment of United States practice relating to treaties, before examining tikanga Māori to consider how its core values might offer guidance on the continuing relevance of the Treaty. Finally, the article looks to contributions from political philosophy relating to the political morality of Treaty-based intercultural justice.